Comparative evaluation of lysolecithin from rice bran oil vis-à-vis lipotropic agents in broiler chicken diet - RAJU, M V L N; CHAKRABARTI, P P; SUJATHA, V; REDDY, J R C; RAMA RAO, S V; RAO, B V S K; PANDA, A K; DEVI, B L A PRABHAVATHI; SUNDER, G SHYAM; PRASAD, R B N (The Indian Journal of Animal Sciences, 2017)
The possibility of using lysolecithin from rice bran oil (LL) as a lipotropic agent was explored in the diet of broiler chickens. The LL was evaluated at 0.1 and 0.5% levels in diet vis-à-vis choline chloride, betaine or a commercial LL (0.1% of any) in broiler chickens (270) from 0 to 35 d of age. The diets were isonitrogenous and isocaloric. Body weight at 35 d was significantly higher in the group fed betaine, while LL showed no effect on growth, feed consumption, serum cholesterol concentration, slaughter variables and liver protein, and fat contents in comparison to control. The serum concentration of triglycerides at 35 d of age, however, decreased significantly with betaine, commercial LL and rice bran oil LL at both the levels. It is concluded that rice bran oil LL at dietary levels upto 0.5% showed no adverse effect on performance and reduced serum triglycerides content in broiler chickens, while betaine improved body weight.